Association Between Objectively Assessed Sleep and Depressive Symptoms During Pregnancy and Post-partum - Pitsillos, Tryfonas; Wikström, Anna-Karin; Skalkidou, Alkistis; Derntl, Birgit; Hallschmid, Manfred; Lutz, Nicolas D.; Ngai, Edith; Sundström Poromaa, Inger; Wikman, Anna (Frontiers in Global Women's Health, 2022)
Introduction: Sleep problems are common in pregnancy but many studies have relied only on self-reported sleep measures. We studied the association between objectively measured sleep and peripartum depressive symptoms in pregnant women. Material and methods: Sleep was assessed using Actiwatch accelerometers in a sample of 163 pregnant women in the late first (weeks 11-15) or early second trimester (weeks 16-19). Depressive symptoms were assessed in gestational weeks 17, 32 and at six weeks post-partum using the Edinburgh Postnatal Depression Scale (EPDS). Multiple linear regression and logistic regression analyses, adjusting for age, BMI, pre-pregnancy smoking, mental health problems, trimester and season of sleep assessment were carried out to test the association between sleep and depression. Sleep was measured by total sleep time and sleep efficiency, whereas depression was indicated by depressive symptoms and depression caseness. Results are presented as unstandardized beta (B) coefficients or adjusted odds ratios (AOR) and 95% confidence intervals (CI). Results: Total sleep time ranged from three to nine hours (mean 7.1, SD 0.9) and average sleep efficiency was 83% (SD 6.0). Women with the shortest total sleep time, i.e., in the lowest quartile (< 6.66 hours), reported higher depressive symptoms during pregnancy (week 17, B=2.13, 95% CI 0.30 – 3.96; week 32, B=1.70, 95% CI 0.03 – 3.37) but not post-partum. Their probability to screen positive for depression in gestational week 17 was increased more than three-fold (AOR=3.46, 95% CI 1.07 – 11.51) but unchanged with regards to gestational week 32 or six weeks post-partum. Sleep efficiency was not associated with depressive symptoms at any stage of pregnancy or post-partum. Discussion: In one of the few studies to use objective sleep measures to date, mental health of pregnant women appeared to be affected by shortened sleep, with total sleep time being negatively associated with depressive symptoms in the early second and third trimester. This finding highlights the relevance of identifying and treating sleep impairments in pregnant women early during antenatal care to reduce the risk of concomitant depression.